FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT SUKUK YANG DITINJAU DARI FAKTOR AKUNTANSI DAN NON AKUNTANSI - Rosi Raimuna; Evi Mutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This research is empirical, where the purpose of this study was to examine the effect of leverage, liquidity, age sukuk and guarantee bonds jointly on the rating sukuk effect of leverage on the ranking of sukuk, the effect of liquidity on the ranking of sukuk, the effect of the age of sukuk on the ranking of securities and the effect of collateral the sukuk sukuk ratings. The population used in this study is the population in this study is the sharia company registered in JII during the period 2012-2015 which amounted to 30 issuers. Sampling was done by sampling purvosive method, wherein the sample selection was based on certain characteristics that are considered to have characteristics of the population that has been previously known. So that the number of the selected sample as many as 12 companies listed in JII sharia which presents the annual financial statements since 2012-2015. The results of this study explains that leverage, liquidity, age sukuk and sukuk guarantee jointly affect the ratings on the companies issuing sukuk sukuk registered in JII the period 2012-2015. Then the partial results of the study also menunjkkan that leverrage does not affect the rating on the company that issued sukuk sukuk registered in JII period 2012-2015, liquidity does not affect the rating on the company that issued sukuk sukuk registered in JII the period 2012-2015, the age of sukuk affect the rating on the company that issued sukuk sukuk registered in the period 2012-2015 and guarantee JII sukuk sukuk affect the rating on the company that issued sukuk registered in JII period 2012-2015.